Awareness and attitude among parents of primary school students towards screen time in children - Shirley, S. Alph; Kumar, S. Santha (International Journal of Contemporary Pediatrics, 2019)
Background: Screen time behavior in young children is highly influenced by parental attitude towards screen time. The objective of this study is to assess the awareness and attitude among parents of primary school students in the state of Tamil Nadu, India towards screen time in children. Methods: This cross-sectional observational study was conducted in the state of Tamil Nadu, India among 134 parents of primary school children. Data collected using a predesigned questionnaire were analyzed using suitable statistical methods. Results: Of the 134 participants, 48.5% were fathers and 51.5% mothers. Majority (77.6%) were in the age group of 24 to 35 years. Only 3.7% of the participants were aware of the exact screen time guidelines in children. 93.3% of the participants felt that it was important to limit screen time in children. 84.3% of the participants believed that the content of screen time should be controlled in children. 82.1% of parents felt that they should co view media with their children. 65.7% of the participants believed that the ideal screen time in children per day is 1 to 2 hours. 82.1% of the participants believed that using screen time as a replacement for caretaker was an important reason for increasing screen time. The awareness of adverse effects of increased screen time was high among the participants. 91.8% of the participants believed that establishing limits for screen time in children was the most efficient way to limit screen time in children. 89.6 % believed that increasing awareness among children was important. Conclusions: In this study, we conclude that majority of the parents were aware of the adverse effects of increasing screen time and want to establish healthy screen time behaviours in children.